Envolvimento da via do óxido nítrico na resposta vasodilatadora induzida pelo nitrato tetra-hidrofurfurilíco (NTHF) em artéria mesentérica superior de Rato - Alustau, Maria do Carmo de (2010)
The organic nitrates are the most commonly nitric oxide (NO) donors used in the treatment of cardiovascular diseases, mainly due the pronounced vasodilator effect. The purpose of this study was to evaluate the vascular effects of tetrahydrofurfuryl nitrate (NTHF), an organic nitrate derivated from the sugarcane s synthetic route. In rat mesenteric artery rings, pre-contracted with phenylephrine 10 μM, NTHF induced concentration-dependent (1 pM-10 μM) vasodilatation, with intact endothelium (Maximum Response = 84 ± 5.3%, pD2 = 7.86 ± 0.22) or endothelium removal, NTHF effects were no attenuated (MR = 100 ± 6.1%, pD2 = 7.39 ± 0.15), suggesting an independent mechanism of endothelium-derived vasoactive factors. The subsequent experiments were performed in rings without endothelium. After pre-incubation of 3 mM NAC, a reactive oxygen species (ROS) scavenger, the response was potentiated (pD2 = 8.32 ± 0.18), a common profile of compounds producing NO. However, when pre-incubated with L-NAME 100 μM, a NOS inhibitor, there was a decrease in the potency (pD2 = 6.62 ± 0.15), suggesting an involvement of this enzyme in the NTHF vascular response. By using scavenger NO radical, hydroxocobalamin 30 μM or carboxy-PTIO 300 μM, the efficacy was attenuated (MR = 66 ± 9.2% and 32 ± 6.2%, respectively), suggesting an involvement of this NO form in the NTHF vasodilator response. In the presence of cyanamide 1 mM, an aldehyde dehydrogenase (ALDH) inhibitor, or ODQ 10 μM, a soluble guanylate cyclase (sGC) inhibitor, there was a significative maximum response s reduction (MR = 29 ± 9.5% and 22 ± 4.6, respectively), indicating an involvement of these enzymes in the NTHF vasodilator mechanism. After exposure to high concentrations of extracellular K+, KCl 80 or 20 mM, the NTHF effect was significantly attenuated (MR = 49 ± 3.8%; 59 ± 9.5%, respectively), a characteristic of substances that act by activating K+ channels. This effect was confirmed after the use of tetraethylammonium (TEA) 3 mM (MR = 31 ± 5.0%), a non-selective K+ channel blocker. In the presence of TEA 1 mM, which at this concentration selectively blocks the BKCa, the vasodilatation was significantly attenuated (MR = 38 ± 8.3%), suggesting the involvement of these channels in the nitrate vasorelaxant effect. This hypothesis was reinforced following the use of 4-aminopyridine 1 mM (MR = 81 ± 8.5%), a KV blocker, glibenclamide 10 μM (MR = 97 ± 9.0%), a KATP blocker, or BaCl2 30 μM (MR = 94 ± 4.9%), a KIR blocker, which did not alter the NTHF vasodilator response. After NTHF (10 μM) incubation for 60 min, the vasodilatation was not changed, indicating that in this concentration this nitrate does not induce vascular tolerance. In conclusion, the NTHF cause vasodilatation, probably by promoting the NO radical release, involving the activation of NOS, ALDH, sGC and BKCa.